Toward Simultaneous Achievement of Outstanding Durability and Photoelectrochemical Reaction in Cu2O Photocathodes via Electrochemically Designed Resistive Switching (Adv. Energy Mater. 39/2021). Issue 39 (21st October 2021) - Kim, Dong Su; Kim, Young Been; Choi, Ji Hoon; Suh, Hee Won; Lee, Hak Hyeon; Lee, Kun Woong; Jung, Sung Hyeon; Kim, Jeong Jae; Deshpande, Nishad G.; Cho, Hyung Koun
Abstract : Resistive Switching In article number 2101905, Hyung Koun Cho and co‐workers solve the trade‐off issue between photo‐charge transport and stability originating from the use of insulating protection layers. The electrochemical forming process suggested for the TiO2 protection layer on photocathodes draws inspiration from typical resistive switching behaviors in resistive‐type memory with metal/insulator/metal (MIM) structures. From the electrochemical filament forming process and selective Pt‐photoelectrodeposition on filaments, the Cu2 O/AZO/TiO2 photocathodes exhibit an unprecedented photocurrent density and open‐circuit potential and produce vigorous hydrogen and oxygen evolution.